200k views
4 votes
3 - 4x = 6x + 93

Please help with this question

2 Answers

6 votes

X=-9

Step-by-step

Simplifying

3 + -4x = 6x + 93

Reorder the terms:

3 + -4x = 93 + 6x

Solving

3 + -4x = 93 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.

3 + -4x + -6x = 93 + 6x + -6x

Combine like terms: -4x + -6x = -10x

3 + -10x = 93 + 6x + -6x

Combine like terms: 6x + -6x = 0

3 + -10x = 93 + 0

3 + -10x = 93

Add '-3' to each side of the equation.

3 + -3 + -10x = 93 + -3

Combine like terms: 3 + -3 = 0

0 + -10x = 93 + -3

-10x = 93 + -3

Combine like terms: 93 + -3 = 90

-10x = 90

Divide each side by '-10'.

x = -9

Simplifying

x = -9

User Sathya Narayanan
by
4.8k points
5 votes

Answer:

-9

Explanation:

User Sota  Sugiura
by
4.7k points